Protein crystallisation in space. - Universiti Putra Malaysia, Research Management Centre (Research Management Centre, Universiti Putra Malaysia, 2009)
Industrial biotechnology is a multi-disciplinary area employing biotechnology knowledge for industrial and commercialisation purposes. One of the focal practices includes the production of industrial products through the use of cells or component of cells namely enzymes. Industrial enzymes of microbial origin are highly demanded due to their applications in a wide variety of processes. Enzyme-mediated reactions are attractive alternatives to the more tedious and expensive chemical methods. Being high in specific activity, efficiency and biodegradability coupled with the low level by-product formations and the capability to work under mild conditions, enzymes are widely used in a range of applications such as in detergent, food and feed industries, human and animal health, waste treatment and the production of fine chemicals.